An investigation on machine learning predictive accuracy improvement and uncertainty reduction using VAE-based data augmentation - Alsafadi, Farah; Yaseen, Mahmoud; Wu, Xu (Nuclear engineering and design, 2025)
The confluence of ultrafast computers with large memory, rapid progress in Machine Learning (ML) algorithms, and the availability of large datasets place multiple engineering fields at the threshold of dramatic progress. However, a unique challenge in nuclear engineering is data scarcity because experimentation on nuclear systems is usually more expensive and time-consuming than most other disciplines. One potential way to resolve the data scarcity issue is deep generative learning, which uses certain ML models to learn the underlying distribution of existing data and generate synthetic samples that resemble the real data. In this way, one can significantly expand the dataset to train more accurate predictive ML models. In this study, our objective is to evaluate the effectiveness of data augmentation using variational autoencoder (VAE)-based deep generative models. We investigated whether the data augmentation leads to improved accuracy in the predictions of a deep neural network (DNN) model trained using the augmented data. Additionally, the DNN prediction uncertainties are quantified using Bayesian Neural Networks (BNN) and conformal prediction (CP) to assess the impact on predictive uncertainty reduction. To test the proposed methodology, we used TRACE simulations of steady-state void fraction data based on the NUPEC Boiling Water Reactor Full-size Fine-mesh Bundle Test (BFBT) benchmark. We found that augmenting the training dataset using VAEs has improved the DNN model’s predictive accuracy, improved the prediction confidence intervals, and reduced the prediction uncertainties. •This paper evaluates the effectiveness of data augmentation using VAE-based DGM.•We investigated the effect of data augmentation on the performance of DNN.•UQ was performed using Bayesian Neural Networks and conformal prediction.•TRACE simulations of steady-state void fraction dataset was used.•Data augmentation using VAEs has improved the DNN accuracy, and reduced uncertainties.